2009
DOI: 10.1111/j.1440-1681.2008.05069.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac‐specific Overexpression of the Human Short Clc‐3 Chloride Channel Isoform in Mice

Abstract: 1. ClC-3 has been proposed as a molecular candidate responsible for volume-sensitive outwardly rectifying anion channels (VSOAC) in cardiac and smooth muscle cells. To further test this hypothesis, we produced a novel line of transgenic mice with cardiac-specific overexpression of the human short ClC-3 isoform (hsClC-3). 2. Northern and western blot analyses demonstrated that mRNA and protein levels of the short isoform (sClC-3) in the heart were significantly increased in hsClC-3-overexpressing (OE) mice comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 36 publications
5
28
0
1
Order By: Relevance
“…Membrane-For ClC-3 to play a role in cell migration (8,11,35), proliferation (9,17,36), and volume regulation (37,38), we hypothesize that it is at least partially expressed on the cell membrane. Using confocal imaging, we found that ClC-3 colocalizes with cortical actin at the cell membrane (Fig.…”
Section: Expression Of Clc-3 On the Plasmamentioning
confidence: 99%
“…Membrane-For ClC-3 to play a role in cell migration (8,11,35), proliferation (9,17,36), and volume regulation (37,38), we hypothesize that it is at least partially expressed on the cell membrane. Using confocal imaging, we found that ClC-3 colocalizes with cortical actin at the cell membrane (Fig.…”
Section: Expression Of Clc-3 On the Plasmamentioning
confidence: 99%
“…Pendrin, which is an exchanger that transports anions such as Cl Ϫ , I Ϫ , and HCO 3 Ϫ , is involved in the secretion of I Ϫ across the apical membrane of thyroid follicular epithelial cells (24,50,51,53,56,66). In addition to pendrin, several other I Ϫ -permeable transporters may contribute to I Ϫ transport including the anion/proton exchangers, ClC-3 and ClC-5, and the anion channels Cftr and Slc26a7 (6,19,40,61,65). Expression levels of pendrin in the murine thyroid have been found to be ϳ50-fold less than in the kidney (61).…”
mentioning
confidence: 99%
“…HL-1 cells show RVD response following hypotonic challenge, similar to responses seen in other cardiac atrial cells [16]. Moreover, HL-1 cardiac cells show abundant RVI responses.…”
Section: Discussionmentioning
confidence: 62%
“…The RVD response in cardiac myocytes has been studied from the following models: embryonic chicken, neonatal rat, guinea pig, rabbit adult ventricular myocytes and mouse adult atrial myocytes [10,11,12,13,14,15,16]. Cultured chick embryo cardiac myocytes [17,18], ventricular rat myocytes [15], adult rabbit ventricular myocytes [19] and mouse atrial myocytes [16] can exhibit RVD. However, others reported the absence of spontaneous RVD in neonatal rat and guinea pig cardiac myocytes [10,13,20,21].…”
Section: Introductionmentioning
confidence: 99%